Gender equality in context: Policies and practices in Switzerland. - (:unkn) unknown (B. Budrich, 2016)
Gender Equality has not yet been achieved in many western countries. Switzerland in particular has failed as a forerunner in integrating women in politics and economy. Taking Switzerland as a case study, the authors critically reflect the state of gender equality in different policy areas such as education, family and labour. The collection of articles reveals how gender policies and cultural contexts interact with social practices of gender (in)equality. They also outline the gender(ed) effects of recent changes and reform strategies for scientists, politicians and practitioners. The book provides nuanced insight into how gender policies and cultural contexts interact with social practices of gender (in)equality and reflects the media and public reception of scientific studies on gender inequality. It is directed to social and political scientists and yields important information on effective strategies and their relevance to gender equality for politicians and practitioners today.
Keywords: Sozialwesen; Soziologie; Geschlechtergerechtigkeit; Geschlechterpolitik